Cultura organizacional para el desarrollo social sostenible en microempresas. Diseño de un instrumento para su evaluación - Perla Angélica Petrilli-Cambambia; Luis Gibran Juárez-Hernández; Sergio Raúl Herrera-Meza (Revista Iberoamericana de Estudios de Desarrollo)
The instruments to evaluate the organizational culture are oriented to analyze it from an economic perspective, and it is emphasized that they are mainly directed towards small and medium-sized companies. Therefore, at present an instrument was designed and validated to assess the organizational culture of microenterprises towards sustainable social development. The instrument was designed as an analytical rubric and integrated the dimensions of planning, leadership, and wellbeing. After its design, it was reviewed by 3 experts, and evaluated by 21 others. Finally, the instrument was piloted with micro entrepreneurs. The review and evaluation of the instrument revealed the belonging of items to the dimensions, and validity of their content (Aiken’s V > 0.75, VI > 0.65, and CVI > 0.80). The piloting revealed that the instrument has a good degree of compression for the target population. It is concluded that the instrument is relevant and valid for the purpose for which it was designed.